The Difference between Corporate Rating Migration Probability during Economic Contraction and Expansion in Indonesia - Ramadhani, Remuni El; Rahim, Rida; Adrianto, Fajri (Image : Jurnal Riset Manajemen, 2024)
Corporate Rating is one of the tools of Signaling Theory, expected to provide clear and standardized signals of a company’s financial health and credit risk. However, according to the experts, the regulation of Corporate Rating issuance by Credit Rating Agency (CRA) becomes a hindrance to the timeliness of company information updates, especially during sudden large-scale economic shifts. Based on this issue, this research aims to examine the differences between Corporate Rating migration probabilities under two different economic conditions: contraction and expansion. Before conducted hypothesis testing, the secondary data from 73 sample companies were processed using Markov-Switching Autoregressive (MSVAR) and Multinomial Logistic Regression methods. Ther results of this study shows that there is no difference in the probability of a Corporate Rating downgrade during both economic conditions. On the other side, the probability of a Corporate Rating upgrade is smaller during economic contraction, and there is a difference in the probability of a Corporate Rating remained unchange between both economic conditions.